Sobre as experiências de comensalidades de imigrantes brasileiros e paraenses em Barcelona - PICANÇO, Miguel de Nazaré Brito (Universidade Federal do Pará, 2021)
This article is of an ethnographic nature and falls under the scope of my Post-doctorate in Anthropology of Food, an instance carried out from July 2018 to January 2019, at the Observatory of Food, at the University of Barcelona, whose objective is describe and analyze, through textual and imagery narratives, the experiences of commensalities enlivened by Brazilians, in particular by paraenses, who live in Barcelona. Through field observation, conversations and interviews, it can be noted that the eating behaviors of immigrants living in Barcelona constitute political resources of resistance and affirmation in relation to other food contexts.